Solow in Transition : Macro and Micro Determinants of Savings in Armenia - Coulibaly, Souleymane; Diaby, Mohamed (World Bank, Washington, DC, 2013)
This paper analyzes and reconciles macro and micro evidence on savings and factors that affect savings, as well as possible policy implications. At the aggregate level, the main question is how savings are affected by growth and macroeconomic policies and variables (fiscal policy, exchange rate, for example) and the breadth of financial markets. Some of these macro determinants can be reconciled with microeconomic evidence of the savings behavior of households. Using macroeconomic quarterly data and household survey data, the analysis explores the determinants of the savings rate at the macroeconomic and microeconomic levels, using the typical econometric models used in the literature (long-term co-integration relation and short-term error correction model for the macro determinants; linear multivariate models for the micro determinants). The long-term relationship indicates that a 10-percent increase in gross domestic product per capita would add 3.7 percentage points to the savings rate in the long run. The short-term relationship depicts a strong catch-up process to the long-run equilibrium, with quarterly changes in gross domestic product per capita and openness strongly correlated with quarterly changes in the savings rate. The characteristics of households that represent the volatility of expected income, such as education and access to borrowing or remittances, significantly impact saving rates. The macroeconomic and microeconomic analyses of the determinants of saving rates in Armenia point to three policy areas: the macroeconomic environment, the financial sector, and the role of remittances.